(untitled) - Bell, Douglas (Harlow, England, 2005)
Novice programers will learn how to write Java programs, how to run them as free-standing programs, and how to invoke a Java program from a Web browser with this text on essentials of Java. Basic programming concepts are introduced early, followed by event-driven programming and an introduction to object-oriented design. Exercises and self- tests are included. This third edition uses UML throughout, and offers an introduction to Swing and other advanced features.
Keywords: Java ( computer programming language )